161. A crowd-knowledge-based analysis of DVHs in SBRT: First steps towards a national virtual audit. (December 2018) - Savini, A.; Fusella, M.; Esposito, M.; Ardu, V.; Benecchi, G.; Bergantin, A.; Borzi, G.R.; Bresciani, S.; Cagni, E.; Carbonini, C.; Casati, M.; Clemente, S.; et al.
Abstract : Purpose: Currently, most of the multicenter analyses on treatment planning rely on the extraction of selected data from the DVH of each plan. A grouped analysis can be biased due to different algorithms implemented in different TPSs used to generate the DVH. In this work we used a consistent method to present a preliminary analysis of multiple data coming from a national survey on stereotactic body radiotherapy (SBRT) planning. Methods: A single spine case was shared among 36 radiation oncology centers. The dose prescription was 30 Gy in 3 fractions with specific constraints on target coverage and dose to nearby organs at risk. Data were collected in DICOM-RT format. A script was developed in R language using the RadOnc R-Package for recalculating the DVHs using the same algorithm. Specific DVH points (V30Gy, D90%, D2%) collected from the centers were compared with those recalculated with RadOnc. A grouped analysis of recalculated DVHs was performed therefore eliminating the bias due to different DVH calculation algorithms. Results: Differences between collected and recalculated DVHs were minimal, however in some cases deviations up to 1.5% were observed. The multiple-DVH analysis showed a notable variability on target dose level (Fig. 1), up to 150% likely related to constraints on target coverage and SBRT technique. This variability was caused mainly by different planning optimization strategies, rather than by the use of a specific treatment technology. Conclusions: The observed variability suggests that comparable standards in patient treatment among different centers can be obtained if a consistent high-level data sharing capability is granted. In the strive to harmonize the planning process, this analysis constitutes a first step toward the creation of a platform of crowd-knowledge-based planning guidelines. This platform could represent a high-quality benchmark for those centers that are willing to implement SBRT techniques (concept expressed in Fig. 1).